The Efficient Antiviral Response of A549 Cells Is Enhanced When Mitochondrial Respiration Is Promoted - Grégorie Lebeau; Daed El Safadi; Aurélie Paulo-Ramos; Mathilde Hoareau; Philippe Desprès; Pascale Krejbich-Trotot; Florian Chouchou; Marjolaine Roche; Wildriss Viranaicken (Pathogens, 2022)
When exposed to a viral infection, the attacked cells promptly set up defense mechanisms. As part of the antiviral responses, the innate immune interferon pathway and associated interferon-stimulated genes notably allow the production of proteins bearing antiviral activity. Numerous viruses are able to evade the interferon response, highlighting the importance of controlling this pathway to ensure their efficient replication. Several viruses are also known to manipulate the metabolism of infected cells to optimize the availability of amino acids, nucleotides, and lipids. They then benefit from a reprogramming of the metabolism that favors glycolysis instead of mitochondrial respiration. Given the increasingly discussed crosstalk between metabolism and innate immunity, we wondered whether this switch from glycolysis to mitochondrial respiration would be beneficial or deleterious for an efficient antiviral response. We used a cell-based model of metabolic reprogramming. Interestingly, we showed that increased mitochondrial respiration was associated with an enhanced interferon response following polyriboinosinic:polyribocytidylic acid (poly:IC) stimulation. This suggests that during viral infection, the metabolic reprogramming towards glycolysis is also part of the virus’ strategies to inhibit the antiviral response.